Paleozoic tectonothermal evolution of the Jinchuan Ni-Cu sulfide deposit, NW China: New constraints from 40Ar/39Ar and (U-Th)/He thermochronology. (1st July 2023) - Tao, Ni; Duan, Jun; Danišík, Martin; Jiao, Jiangang; Dong, Yunpeng; Evans, Noreen J.; Gao, Yalin; Jiao, Ruohong; Rahn, Meinert
Highlights: The Ediacaran–late Cambrian amphibolite facies metamorphism in Jinchuan. Devonian extensional exhumation during the spreading of the North Qilian Ocean. Syn-orogenic (Qilian Orogeny) magmatic reheating up to ∼400 ˚C in Silurian. Protracted late Paleozoic cooling to <150 ˚C related with Qilian orogenic collapse. Abstract: The world's third largest and China's largest magmatic Ni-Cu sulfide deposit – the Jinchuan ore deposit, is hosted in the Proterozoic basement of the Longshoushan Terrane, a NW-extending elongated orogen on the southwestern margin of the North China Craton. The Paleozoic tectonothermal history of the Jinchuan Ni-Cu sulfide deposit is crucial to understand ore formation and spatial occurrence in the area. Accordingly, this study applies multimineral (hornblende, biotite, and K-feldspar) 40 Ar/ 39 Ar and zircon (U-Th)/He thermochronology to the Neoproterozoic Jinchuan ore-hosting intrusion, as well as to the Paleoproterozoic migmatitic country rocks and an early Paleozoic granitic intrusion in the Longshoushan Terrane. Hornblende 40 Ar/ 39 Ar ages of 543 Ma and 489 Ma from the migmatitic country rocks constrain the age of amphibolite facies metamorphism in Jinchuan to the Ediacaran to late Cambrian. The presence of nearby Silurian to Devonian sediments suggests that the Jinchuan ore deposit was exhumed to the surface by the Silurian. Exhumation occurred in an extensional setting during the spreading and subduction of the North Qilian Ocean. Syn-orogenic (Qilian Orogeny) magmatic reheating up to ∼ 400 ˚C in the Silurian occurred in the middle of the pre-Silurian surface exposure and Devonian thermal event as illustrated by biotite 40 Ar/ 39 Ar plateau ages of 406 Ma and 380 Ma, respectively. The late Carboniferous plagioclase and K-feldspar 40 Ar/ 39 Ar mini plateau ages of ca. 318 Ma and ca. 301 Ma, together with Mississippian (ca. 334 Ma) to Guadalupian (ca. 272 Ma) zircon (U-Th)/He mean ages, suggest protracted late Paleozoic cooling to < 150 ˚C, associated with the Qilian orogenic collapse.